2020
DOI: 10.1021/acs.iecr.0c03817
|View full text |Cite
|
Sign up to set email alerts
|

Extended Graphical Approach for the Deployment of Negative Emission Technologies

Abstract: It is critical to limit global warming to 1.5 °C by the year 2100 to minimize catastrophic impacts. The increased integration of renewable energy, alongside CO2 capture and storage (CCS) deployment in energy planning, remains as a key mitigation technique in minimizing climate change impacts. Although renewable energy generation approaches the ideal of a carbon-neutral system, other processes such as fossil fuel-based generation, manufacturing, and transportation are net-carbon positive. Additionally, renewabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Global warming is recognized as the main inherent cause responsible for climate change, rapid rise in sea level, and related harms to the environment. , In addition, the increase of carbon dioxide in the atmosphere from 300 to 385 ppm, the highest content in the past 2.1 million years, triggers the global warming issues. , As a result, reducing CO 2 in the atmosphere is the inevitable way to protect the environment where all lives on earth rely on. Several approaches have been proposed to achieve CO 2 reduction, such as directly adsorbing CO 2 in the air using highly specific surface materials, CO 2 geological sequestration, and enhancing oil recovery by injecting CO 2 into oil formation .…”
Section: Introductionmentioning
confidence: 99%
“…Global warming is recognized as the main inherent cause responsible for climate change, rapid rise in sea level, and related harms to the environment. , In addition, the increase of carbon dioxide in the atmosphere from 300 to 385 ppm, the highest content in the past 2.1 million years, triggers the global warming issues. , As a result, reducing CO 2 in the atmosphere is the inevitable way to protect the environment where all lives on earth rely on. Several approaches have been proposed to achieve CO 2 reduction, such as directly adsorbing CO 2 in the air using highly specific surface materials, CO 2 geological sequestration, and enhancing oil recovery by injecting CO 2 into oil formation .…”
Section: Introductionmentioning
confidence: 99%
“…For example, CEPA has been extended to the planning of CCS systems [83] and more recently to NETs deployment planning (see Fig 3A; [84]). Derivative graphical [84,85] and algebraic techniques [86] have been proposed for the optimum deployment of NETs. A CEPA study of the UK's decarbonization concluded that net-zero emissions can be achieved with BECCS [87].…”
Section: Graphical and Algebraic Pinch Analysis Extensionsmentioning
confidence: 99%
“…Note that these technologies are not plant-specific. Instead, the cumulative deployment of these mitigation technologies is determined for period k. The deployment of renewable energy source r (FC k,r ), EP-NETs technology p (FEP k,p ) and EC-NETs technology q (FEC k,q ) in period k are constrained by the availability of each technology, as demonstrated in Equation ( 16), Equation (17) and Equation (18), respectively:…”
Section: Mathematical Formulation Of Deco2mentioning
confidence: 99%
“…In the past, mathematical programming and pinch-based approaches were developed to consider the deployment of NETs during carbon-constrained energy planning. For the latter approach, the graphical targeting technique [6] was extended to incorporate EP-NETs during energy planning [17]. Recognising that a portfolio of NETs would be required to accelerate CDR, this work was later revamped for the combined deployment of both EP-NETs and EC-NETs [18].…”
Section: Introductionmentioning
confidence: 99%